Bangladesh : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
Satisfactory progress has been made so far under the first-year poverty reduction and growth facility and the program is on track. Turning this progress into faster and lasting growth requires deeper reform to improve the investment climate and credible action to strengthen governance. The recent shift in the stance of macroeconomic policies to support growth is timely. The targeted increase in the budget for infrastructure and social spending is well considered. Bangladesh's record under the program so far has been positive overall.